Congenital Short Bowel Syndrome - Saha, Amar Kumar; Haque, Sheikh Sayidul; Biswas, Sunil Kumar; Ali, Md Barkot (Journal of Surgical Sciences, 2019)
Congenital short bowel syndrome (SBS) is a rare congen.it.al disease, Only about 37 cases were reported. Infants usually present with failure to 'thrive, recurrent vomiting and or diarrhoea. It is associated with significant mortality and morbidity, High degree of suspicion is necessary to diagnose this condition promptly. Early initiation of parenteral nutrition or surgery may result in a favorable outcome. We treated a case of infant aged eight-weeks presented with recurrent bilious vomiting and failure to thrive. On Laparotomy it was found that the baby had very short small bowel with malrotation. This case was reported and reviewed. Journal of Surgical Sciences (2014) Vol. 18 (1) : 35-37